Six Gynecological Cancer Patients Infected With SARS-CoV-2 After Surgery or Radio-/Chemo-Therapy Treatment: Case Series - Liu, Chen; Huang, Yuhan; Qin, Tianyu; Guo, Ensong; Wu, Peng; Sun, Chaoyang; Chen, Gang (Frontiers in Oncology, 2020)
Objective Recently, the number of gynecological cancer patients infected with SARS-CoV-2 has been increasing. This article was committed to studying the influence of gynecological tumor treatment history compared to the Coronavirus Disease 2019 (COVID-19), which was of great significance for the treatment of gynecological cancer patients during the outbreak of COVID-19. Methods We retrospectively analyzed the diagnosis and treatment of six gynecological cancer patients infected with SARS-CoV-2 in Tongji Hospital in Wuhan from January 30 to March 25, 2020. To better explain the treatment of gynecological cancer patients during the epidemic of COVID-19, we summarized the case characteristics, auxiliary examination, treatment plan, and outcome of these six patients. Results We observed a high rate of nosocomial SARS-CoV-2 infection among these six gynecological cancer patients, who were in a low immune state. Also, due to the influence of cancer treatment history, COVID-19-related atypical symptoms became the first symptom of COVID-19 in some cases, which increased the difficulty of diagnosis. Furthermore, in terms of treatment for these cases, immune boosters and reagents that raised white blood cells were applied, except for in symptomatic antiviral treatment. At present, all patients in this study were discharged from the hospital with a good prognosis. Conclusion After cancer-related treatment, the gynecological cancer patients became more susceptible to COVID-19. Besides, the history of cancer treatment made the diagnosis of COVID-19 difficult, which also affected the treatment of COVID-19. Therefore, we put forward the corresponding therapy suggestions for gynecological cancer patients during the outbreak of COVID-19.